Chemometric analysis of the influence of mechanical activation on the mica quality parameters. Issue 7 (August 2015) - Terzić, Anja; Pezo, Lato; Andrić, Ljubiša
Abstract: The differences in the set of the process parameters measured before and after mica mechanical activation and their influence on the grain size distribution related characteristics have been studied. The modification of the behavior for activated samples has been correlated to the particle size distribution effect produced by activation via an ultra centrifugal mill. The mechanical treatments are energetically and economically unsustainable procedures, therefore the mica activation was optimized on basis of assessment of the process variables effect on the final quality of product parameters. Response surface method, standard score analysis and principal component analysis were used as means of the optimization. Developed models showed r 2 values in the range of 0.816–0.988 and they were able to accurately predict quality parameters in a wide range of processing parameters. Standard score analysis highlighted that the optimal sample was obtained using sieve mesh of 80 μm set of processing parameters (SS=0.81). Multiple comparison tests revealed that the optimal variation in the processing parameters could reduce the negative effect of mica samples inherent properties on the final score and improve activation procedure energetic and economic sustainability.